Gestão de estoques e sua influência no desempenho financeiro: uma análise em empresas de manufatura - Cotomácio, André Carrara (2017)
There are many studies in the literature that have shown the relationship between stock levels and financial performance, through profitability indicators, mostly to US manufacturing firms. However, the influence of the stock and its discrete components (raw material, inventory, production and finished product) in shareholder wealth has not been determined, particularly in the case of companies in Brazilian industrial sector. The present study aims to assess how the maintenance of inventory levels may affect profitability, returns and share performance in order to maximize shareholder wealth. For this purpose, panel data regressions were applied for fixed and random effects, based on financial data from companies which represents Brazilian manufacturing sector, listed in the BM&FBOVESPA Industrials Index (INDX). From the concept that a correct inventory and working capital management are directly linked to a better financial performance, the results show that this hypothesis confirmation or refutation vary according to the financial and inventory management metrics used, respectively, as dependent or independent variables. Another conclusion is that shareholder value creation has greater influence or is better able to isolate the effect of a correct inventory management, when compared to profitability and return metrics, only if linked to raw material or finished products indicators. Although the divergences regarding the influence of inventory and working capital management on financial performance still persist, this is one of the first studies that discuss this issue for Brazilian companies, and more specifically, for manufacturing sector, which represent an important stock portfolio index in the country.